Amphorae from the Roman fort at Gheriat el-Garbia (Libya) - Schimmer, Florian (Rei Cretariae Romanae Fautorum Acta, 2012)
The Roman fort at Gheriat el-Garbia is situated near an oasis in the tripolitanian pre-desert about 280 km south of tripoli on the fringes of the Hamada al-Hamra in Libya. It was built around aD 200 during the expansive frontier policy of Septimius Severus and represents the most important Severan military site of the limes Tripolitanus. While a vexillation of the legio III Augusta from Lambaesis was based in the fort until 238, it has been proposed that the fort was the headquarters of the praepositus limitis (regionis) Tripolitanae between 238 and 270/275 when the garrison abandoned the site.